Boosting photocatalytic CO2 reduction in a ZnS/ZnIn2S4 heterostructure through strain-induced direct Z-scheme and a mechanistic study of molecular CO2 interaction thereon. (March 2022) - Sabbah, Amr; Shown, Indrajit; Qorbani, Mohammad; Fu, Fang-Yu; Lin, Tsai-Yu; Wu, Heng-Liang; Chung, Po-Wen; Wu, Chih-I.; Santiago, Svette Reina Merden; Shen, Ji-Lin; Chen, Kuei-Hsien; Chen, Li-Chyong
Abstract: Employing direct Z-scheme semiconductor heterostructures in photocatalysis offers efficient charge carrier separation and isolation of both redox reactions, thus beneficial to reduce CO2 into solar fuels. Here, a ZnS/ZnIn2 S4 heterostructure, comprising cubic ZnS nanocrystals on hexagonal ZnIn2 S4 (ZIS) nanosheets, is successfully fabricated in a single-pot hydrothermal approach. The composite ZnS/ZnIn2 S4 exhibits microstrain at its interface with an electric field favorable for Z-scheme. At an optimum ratio of Zn:In (~ 1:0.5), an excellent photochemical quantum efficiency of around 0.8% is reached, nearly 200-fold boost compared with pristine ZnS. Electronic levels and band alignments are deduced from ultraviolet photoemission spectroscopy and UV-Vis. Evidence of the direct Z-scheme and carrier dynamics is verified by photo-reduction experiment, along with photoluminescence (PL) and time-resolved PL. Finally, diffuse-reflectance infrared Fourier transformed spectroscopy explores the CO2 and related intermediate species adsorbed on the catalyst during the photocatalytic reaction. This microstrain-induced direct Z-scheme approach opens a new pathway for developing next-generation photocatalysts for CO2 reduction. Graphical Abstract: ga1 Highlights: We demonstrated that a facile single-pot hydrothermal method derived ZnIn2 S4 decorated with ZnS as direct Z-scheme heterostructure. This work covers the in-depth study of the Z-scheme mechanism and strain analysis. We have provided more in-depth explanations of the origin and mechanism of Z-scheme process. The DRIFTS study explores the reaction mechanism and the interaction of CO2 with catalyst during photocatalytic reaction.